Cryptic TCF3 fusions in childhood leukemia: Detection by RNA sequencing. Issue 1 (13th September 2021) - Salim, Mustafa; Heldt, Frederik; Thomay, Kathrin; Lentes, Jana; Behrens, Yvonne Lisa; Kaune, Beate; Möricke, Anja; Cario, Gunnar; Schieck, Maximilian; Hofmann, Winfried; Davenport, Claudia; Steinemann, Doris; et al.
Abstract: Acute lymphoblastic leukemia (ALL) is the most frequent malignancy in childhood and adolescence. In more than 60% of cases of this heterogeneous disease, a genetic marker is identified via cytogenetic or molecular analyses. TCF3 gene fusions occur in 5%–11% of ALL patients. In < 1%, the TCF3 alteration in ALL leads to a TCF3‐HLF fusion gene. Even though this is a very rare event, the detection of a TCF3‐HLF fusion gene is associated with a very poor prognosis with incurable relapses in almost all patients. The frequent TCF3‐PBX1 fusion gene, which is detectable in 5%–10% of childhood B‐cell precursor ALLs and 3.8% of adult B‐cell precursor ALLs, is associated with a rather good prognosis, that is, an observed event‐free 5‐year survival of approximately 85%. Thus, the distinction of the different partner genes fused to TCF3 is essential for risk assessment. To verify RNA sequencing as a tool for detection of known and unknown fusion genes, we screened 200 cases of pediatric B‐cell precursor ALL with "targeted" RNA sequencing in a pilot project in comparison to classical cytogenetic analyses (chromosome R‐banding analysis), fluorescence in situ hybridization, and PCR. We observed a TCF3 fusion gene in 6.5% (13/200) of the patients. Ten (5%) patients displayed a TCF3‐PBX1 fusion gene, two (1%) patients a TCF3‐FLI1 fusion gene, and one (0.5%) patient a TCF3‐HLF fusion gene. For the TCF3 fusions, we obtained discrepant results with the different methods, which are described in the article. Taken together, translocations leading to TCF3 fusion genes might appear cryptic and may remain undetected by a single method.